A family of solution processable ligands and their Re(I) complexes towards light emitting applications. (April 2019) - Klemens, Tomasz; Świtlicka, Anna; Machura, Barbara; Kula, Sławomir; Krompiec, Stanisław; Łaba, Katarzyna; Korzec, Mateusz; Siwy, Mariola; Janeczek, Henryk; Schab-Balcerzak, Ewa; Szalkowski, Marcin; Grzelak, Justyna; et al.
Abstract: A series of triimine ligands incorporating 2, 2′:6′, 2″-terpyridine (terpy), 2, 6-di(thiazol-2-yl)pyridine (dtpy), and 2, 6-di(pyrazin-2-yl)pyridine (dppy) frameworks, as well as their corresponding Re(I) tricarbonyl complexes were successfully designed and synthesized to investigate the impact of the peripheral rings (pyridine, thiazole and pyrazine) and phenyl– or naphthyl–based substituents attached to the triimine skeleton on their photophysical and electroluminescent properties. The experimental studies were accompanied with DFT/TDDFT calculations. DSC investigations showed that both the free ligands and Re(I) complexes melted at high temperature (164–309 °C) and some of them are able to form amorphous materials. CV measurements revealed that energy band gaps calculated on the basis of ionization potential and electron affinity of the Re(I) complexes, which are correlated with energy levels of frontier molecular orbitals, fall in the range of 2.14–2.32 eV, being lower than the corresponding ligands, what makes the complexes promising for organoelectronic applications. The photophysical properties of the synthesized triimine ligands and Re(I) complexes were studied in detail by electronic absorption and emission. In solution they exhibited photoluminescence quantum yields ranging from 0.15% to 84.42% depending on the chemical structure. The presence of pyrazine units significantly reduced ability for radiative emission. All the compounds were emissive also in a solid state. Preliminary tests of electroluminescence ability demonstrated that most of the devices with Re(I) complexes exhibited red or orange emission, while diodes with ligands showed maximum of emission band located mainly in the green region. It should be noticed that diodes with active layer consisting of a neat complex (ITO:PEDOT:PSS/complex/Al) emitted light under applied voltage. Highlights: A series of solution processable ligands and their Re(I) complexes was synthesized. The impact the peripheral rings and substituents attached to the triimine skeleton was studied. Eg of the Re(I) complexes was between 2.14 and 2.32 eV, being lower than the corresponding ligands. The replacement of pyridine and thiazole with pyrazine units reduced luminescence efficiency. The ability for EL of both ligands and complexes was preliminary tested.